Tissue-Specific Approaches Reveal Diverse Metabolic Functions of Rho-Kinase 1 - Landry, Taylor; Shookster, Daniel; Huang, Hu (Frontiers in Endocrinology, 2021)
Rho-kinase 1 (ROCK1) has been implicated in diverse metabolic functions throughout the body, with promising evidence identifying ROCK1 as a therapeutic target in diabetes and obesity. Considering these metabolic roles, several pharmacological inhibitors have been developed to elucidate the mechanisms underlying ROCK1 function. Y27632 and fasudil are two common ROCK1 inhibitors; however, they have varying non-specific selectivity to inhibit other AGC kinase subfamily members and whole-body pharmacological approaches lack tissue-specific insight. As a result, interpretation of studies with these inhibitors is difficult, and alternative approaches are needed to elucidate ROCK1’s tissue specific metabolic functions. Fortunately, recent technological advances utilizing molecular carriers or genetic manipulation have facilitated discovery of ROCK1’s tissue-specific mechanisms of action. In this article, we review the tissue-specific roles of ROCK1 in the regulation of energy balance and substrate utilization. We highlight prominent metabolic roles in liver, adipose, and skeletal muscle, in which ROCK1 regulates energy expenditure, glucose uptake, and lipid metabolism via inhibition of AMPK2α and paradoxical modulation of insulin signaling. Compared to ROCK1’s roles in peripheral tissues, we also describe contradictory functions of ROCK1 in the hypothalamus to increase energy expenditure and decrease food intake via leptin signaling. Furthermore, dysregulated ROCK1 activity in either of these tissues results in metabolic disease phenotypes. Overall, tissue-specific approaches have made great strides in deciphering the many critical metabolic functions of ROCK1 and, ultimately, may facilitate the development of novel treatments for metabolic disorders.